2022
DOI: 10.1007/978-1-0716-2205-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Crop Growth Models and Genomic Prediction

Abstract: Crop growth models (CGMs) consist of multiple equations that represent physiological processes of plants and simulate crop growth dynamically given environmental inputs. Because parameters of CGMs are often genotype-specific, gene effects can be related to environmental inputs through CGMs. Thus, CGMs are attractive tools for predicting genotype by environment (G×E) interactions. This chapter reviews CGMs, genetic analyses using these models, and the status of studies that integrate genomic prediction with CGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…Several studies have indicated that environmental information helps to enhance the prediction of phenotypic performance (Heslot et al 2014;Technow et al 2015;Costa-Neto et al 2021, 2022. When modeling GEI in maize with machine learning, Westhues et al (2021) did not observe much gain when predicting plant height, but the grain yield prediction improved after including environmental information.…”
Section: The Importance Of Environmental Information Should Not Be Un...mentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have indicated that environmental information helps to enhance the prediction of phenotypic performance (Heslot et al 2014;Technow et al 2015;Costa-Neto et al 2021, 2022. When modeling GEI in maize with machine learning, Westhues et al (2021) did not observe much gain when predicting plant height, but the grain yield prediction improved after including environmental information.…”
Section: The Importance Of Environmental Information Should Not Be Un...mentioning
confidence: 98%
“…These environmental data can be applied in enviromics studies by envirotyping the testing locations (Costa-Neto et al 2021, 2022 or in a combined way with biological knowledge through crop growth models to increase accuracy in GP (Heslot et al 2014;Technow et al 2015). In this case, increases of up to 11% in prediction accuracy have been observed (Heslot et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While this study focused on growth curves represented by nonlinear equations, crop growth in response to the environment has been described by a physiological model known as a crop growth model (CGM) [22][23][24][25][26][27][28]. In the context of the CGM, there has been some discussion about the advantages of one-step and two-step models [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…While this study focused on growth curves represented by nonlinear equations, crop growth in response to the environment has been described by a physiological model known as a crop growth model (CGM) [22][23][24][25][26][27][28]. In the context of the CGM, there has been some discussion about the advantages of one-step and two-step models [27,28]. In the two-step model, CGM parameters are first estimated for each variety, and then models for specific genetic analysis, such as QTL analysis, genome-wide association study and genomic prediction, are applied to the estimated parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation